(untitled) (Interdisciplinary Studies Journal, 2025)
This article investigates the student profile from the perspective of teachers in legal education within the context of Professional and Technological Education (EPT), focusing on the technical courses in Occupational Safety, offered in both integrated and subsequent modalities by the Federal Institute of Pernambuco (IFPE). Through a qualitative approach, semi-structured interviews were conducted with teachers from both modalities, aiming to understand the pedagogical and institutional challenges related to the teaching of Law. The results reveal significant heterogeneity among students, both in terms of age range and educational trajectories, as well as socioeconomic contexts, which requires diverse pedagogical practices. Among the difficulties reported by teachers are limitations in reading and interpreting legal texts, previous educational gaps, and insufficient institutional support, such as the lack of effective tutoring and limited interdisciplinary articulation. Despite these obstacles, teachers recognize the transformative potential of legal education in fostering students’ citizenship and critical thinking, especially when classes succeed in establishing connections between content and professional practice. The study highlights the need for robust institutional policies aimed at strengthening continuous teacher training and providing effective pedagogical support to students. Finally, it is observed that legal education in EPT contributes not only to technical qualification but also to the development of citizenship.